2023
DOI: 10.2147/ibpc.s403023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with Hypertension Among Adults on Dolutegravir-Based Antiretroviral Therapy in Uganda: A Cross Sectional Study

Abstract: Introduction Dolutegravir-based anti-retroviral therapy (ART) regimens were rolled out as first line HIV treatment in Uganda due to their tolerability, efficacy and high resistance barrier to human immunodeficiency virus (HIV). They have however been associated with weight gain, dyslipidemia and hyperglycemia which are cardiometabolic risk factors of hypertension. We assessed the prevalence and factors associated with hypertension among adults on dolutegravir regimens. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Our study again revealed that older adults (aged ≥50 years) on DTG-based regimens have slightly higher risk (2%) of developing HTN, even though this difference is not clinically significant. These findings are consistent with what was found in a study in Uganda to determine factors associated with HTN among adults on DTG-based regimen [ 16 , 36 ]. This could be associated with the aging process, which leads to various alterations in the arterial vasculature’s structure and function and reduced blood supply to the heart [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study again revealed that older adults (aged ≥50 years) on DTG-based regimens have slightly higher risk (2%) of developing HTN, even though this difference is not clinically significant. These findings are consistent with what was found in a study in Uganda to determine factors associated with HTN among adults on DTG-based regimen [ 16 , 36 ]. This could be associated with the aging process, which leads to various alterations in the arterial vasculature’s structure and function and reduced blood supply to the heart [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Another study by Brennan et al in South Africa also reported a 14.2 percentage point increase in the risk of HTN in patients exposed to DTG for 12 months compared to those that remained on efavirenz [ 28 ]. Similarly, a cross-sectional study conducted in Uganda reported a prevalence of 27.2% among patients initiated on DTG for a median duration of 28 months [ 16 ]. Results of the New Antiretroviral and Monitoring Strategies in HIV-Infected Adults in Low-Income countries (NAMSAL) study showed a significant increase in BP comparing baseline versus week 192 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations